Analysis of the adaptation potential of the cardiovascular system of students studying in medical specialties - O. N. Pavlova; D. S. Gromova; E. V. Makarova-Gorbacheva; A. I. Budaev; Yu. A. Halitova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Studying the adaptive potential of students is an important way to assess the level of health and early career guidance of future doctors.The purpose of the study is to study the adaptive potential of the cardiovascular system among second-year medical university students.Object and methods. The study involved 507 students of both sexes studying in their second year at Samara State Medical University. At the first stage of the study, anthropometric parameters were studied in all subjects. At the second stage, an analysis of the adaptive potential was carried out by calculating the following indicators: index of functional changes, adaptive potential according to the equation of L.A. Konevskikh, Robinson index.Conclusions. An analysis of the functional state of the cardiovascular system of medical university students revealed that the majority of students already in their second year have a disruption of adaptation processes, which is associated with low functional capabilities of the body, tension in adaptation mechanisms and disruption in the functioning of regulatory systems.